Assessing the Characteristics of Cocoa Vinegar from Pulp Liquids Fermentation by Various Methods - G. P. Ganda Putra; Ni Made Wartini; Luh Putu Trisna Darmayanti (Emerging Challenges in Agriculture and Food Science Vol. 4, 2022)
Pulp liquids, a byproduct of cocoa bean fermentation, have the potential to be used as a raw material for cocoa vinegar. However, additional fermentation is required to optimize the formation of acetic acid. In this section, we will go over how to make vinegar from cocoa pulp liquids. The objectives of this research were (1) to study the effect of the pulp liquid fermentation method on the characteristics of the cocoa vinegar and (2) to determine the optimal fermentation method for the production of cocoa vinegar. We tested several fermentation methods in order to determine the best method for producing distillated cocoa vinegar. Treatment with various fermentation methods, including 1-phase, 2-phase, and natural, was used in this study. Acetic acid (1-phase) fermentation using Acetobacter aceti inoculum, with variations in alcohol additions of 6, 8, 10, and 12%. Alcohol and acetic acid (2-phase) fermentation using Saccharomyces cerevisiae and Acetobacter aceti inoculum, with variations in sugar additions of 4, 6, 8 and 10%. Natural aerobic fermentation is another method of fermentation (without inoculum and carbon source). All subsequent fermentation methods were performed at room temperature for 25 days and were divided into four groups to yield 36 experimental units. The findings revealed that fermentation methods and the addition of sugar or alcohol influenced the characteristics of cocoa vinegar distillate, such as organic acids, total soluble solids (TSS), sugar, salt, alcohol, and acidity (pH). It concludes that single-phase fermentation with 10% alcohol results in higher acetic and propionic acid content of cocoa vinegar distillate, as well as higher TSS and sugar, but lower salt content and acidity (pH).